Determinants of Unemployment among Educated Youth: Empirical Reflections from Twin Cities, Pakistan - Amer, Roha (Journal of Professional Research in Social Sciences, 2025)
Youth unemployment represents a persistent global challenge, particularly within developing economies where its social and economic repercussions are profound. Pakistan is no exception, as a significant proportion of its young population continues to face difficulties in accessing meaningful employment opportunities. This study investigates the determinants of youth unemployment and their relationship with unemployment rates in Pakistan, with a specific focus on the metropolitan regions of Islamabad and Rawalpindi. Data were collected from a sample of 300 individuals aged 18 to 29 years, each possessing a minimum educational qualification of a diploma or associate degree (14 years of education). Logistic regression analysis was applied to identify significant factors influencing unemployment. The results indicate that age has an inverse relationship with unemployment, suggesting that older youth are more likely to be employed. Gender disparities were also evident, with men exhibiting lower unemployment rates compared to women. Furthermore, marital status emerged as a significant determinant, as unmarried individuals were found to be more susceptible to unemployment. Socioeconomic background also influenced outcomes; middle-class respondents demonstrated higher employment rates due to greater adaptability and continuous engagement in the labor market. Conversely, individuals awaiting government job opportunities exhibited higher unemployment levels. The study concludes that technical and vocational skills play a pivotal role in reducing unemployment among educated youth by enhancing employability and aligning qualifications with labor market demands. Policymakers are encouraged to strengthen skill-oriented education and promote private-sector participation to mitigate youth unemployment in Pakistan.